Google Classroom as an alternative during the COVID-19 pandemic: teachers' perceptions. (Revista de Investigaciones Universidad del Quindío, 2022)
Currently, Information and Communication Technologies (ICTs) offer wide access to various educational tools that complement both classroom and online education; therefore, it is the responsibility of institutions to be at the forefront and provide teachers with the necessary technological tools to generate better conditions for meaningful learning. In this sense, the need arises to analyze the use of ICTs during the COVID-19 pandemic as a complement for the teacher in the teaching-learning process. The objective of this research was to analyze the use of Google Classroom during the period March 2020 to February 2021, a tool that supported teachers in communicating with their students at the Universidad Popular de la Chontalpa. For this purpose, a survey was applied to know the perception of 150 teachers of the Economic-Administrative Sciences Division (DCEA) towards the use of the platform. The data analysis was carried out through graphs and their respective description where it was found that most of the teachers accessed the platform to create online classes with students, although their level of knowledge was basic, this software allowed them to maintain interaction with students during the period of suspension of face-to-face classes due to COVID-19; an attitude of acceptance towards its use by teachers and students was perceived. Finally, recommendations were made to continue with teacher training, at intermediate and advanced levels, on the operation and management of the Google Classroom platform, as well as the creation of an area to provide advice to teachers and students in relation to ICTs at the Universidad Popular de la Chontalpa.
Keywords: Gloogle Classroom; COVID-19; teachers